Predictors of Sleep-disordered Breathing in Pregnancy. Issue 1 (March 2019) - Louis, J.M.; Koch, M.A.; Reddy, U.M.; Silver, R.M.; Parker, C.B.; Facco, F.L.; Redline, S.; Nhan-Chang, C.L.; Chung, J.H.; Pien, G.W.; Basner, R.C.; Grobman, W.A.; et al.
Abstract : ( Am J Obstet Gynecol . 2018;218:521.e1–e12) Sleep-disordered breathing (SDB) in pregnancy is associated with an increased risk of complications and adverse outcomes, including preeclampsia, venous thromboembolism, severe maternal morbidity, preterm delivery, and maternal death. Identifying women with SDB is difficult, however, as SDB symptoms are not very specific. The best method for diagnosis of SDB is overnight polysomnography, which is expensive and inconvenient. This study used a large cohort of pregnant women to establish clinically feasible prediction models for SDB.